Analysis of Oil Palm Nursery Business at PT. Merbau Jaya Indah Raya in Lerepako Village, Laeya District, South Konawe Regency, Southeast Sulawesi Province - Nurain; Yusna Indarsyih; Muhammad Aswar Limi (International journal of technology and education research, 2025)
This study aims to: (1) examine the cultivation techniques applied in oil palm seedling farming, and (2) identify the production factors utilized and analyze the production costs involved in the oil palm seedling farming activities at PT. Merbau Jaya Indah Raya, located in Lerepako Village, Laeya Subdistrict, South Konawe Regency, Southeast Sulawesi Province. The research was conducted from January to July 2025. The data used in this study consisted of primary data collected through direct interviews and secondary data obtained from related institutions or agencies. The data analysis method employed was quantitative analysis.The findings of the study revealed that: (1) the oil palm seedling process at PT. Merbau Jaya Indah Raya involves several stages, including the germination process, polybag stage, preparation of planting media, selection of the nursery site, preparation of the Pre-Nursery (PN) area, planting of germinated seeds, maintenance of the Pre-Nursery (PN), preparation of the Main Nursery (MN) area, transfer of seedlings to the Main Nursery (MN), maintenance of the Main Nursery (MN), and preparation for field planting; and (2) the total production cost of the oil palm seedling farming at PT. Merbau Jaya Indah Raya was IDR 322,922,311.90 per year or per production cycle, with an average seedling cost of IDR 16,146.12.